SOCIALIZATION STIMULATION PROGRESSION WITH SOCIALIZATION DEVELOPMENT ON PRE SCHOOL CHILDREN AGE 36 – 47 MONTHS - Yendrizal Jafri; Isna Ovari (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2015)
Introduction. Childs stimulation from the outside environment is form of training or playing. Stimulation is a very important requirement for the growth and development of children. Children who get a lot of targeted stimulation will quickly develop. The purpose of this study was to know the corelation of socialization stimulation progression with the development of preschool children’s. Methods. Research design was Quasi Ekperiment with prospective method. Populations in this study were children aged 36-47 months with number of samples 23 respondents. Research’s instrument used questionnaires and observation sheets. Data were processed by looking at the distribution and frequency, mean value and statistical Chi-Square Test. Result. From the result of research was obtained 1) Stimulation given on early stimulation stag, with good category 47.8%, aftergiven the good category stimulation category 87.0%. 2) Development of socialization with good category was 87.0% on age group 36-47 month. 3) Results of the statistical test shoed that there was correlation of stimulation progression with children’s socialization development. Discussion. Social personal development was strongly infl uenced by environment and interaction among children and parents or other adult childrens. Children development will be optimal when social interaction was suitable according to children at every different stages of developmentKeywords: stimulation, socialization developments, preschool